2022
DOI: 10.1093/ndt/gfac316
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of all-cause mortality for chronic kidney disease patients using four models of machine learning

Abstract: Background The prediction tools developed from general population data to predict all-cause mortality are not adapted to chronic kidney disease (CKD) patients, because this population displays a higher mortality risk. This study aimed to create a clinical prediction tool with good predictive performance to predict the 2-year all-cause mortality of stage-4 or stage-5 CKD patients. Methods The performance of four different mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Nonetheless, there is face validity in this study's findings; it was expected that those with CKD would have a greater burden of frailty, cognitive impairment, and co-occurrence of the two conditions; given their higher prevalence of comorbidities, particularly in vascular disease. Further studies should aim to replicate these findings among those with and without CKD in other, diverse population studies with validated measures of frailty and cognitive function to better compare the magnitude of burden.This diverse, nationally-representative study further corroborates the potential vascular underpinnings of the frailty-cognition link demonstrated in prior studies [27][28][29][30]35]. Our findings support those prior studies in that the strongest associations between frailty and cognitive function were found for executive function and processing speed (Cohen's d = -0.44, 95%CI: -0.60, -0.28) compared to other memory-related domains.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Nonetheless, there is face validity in this study's findings; it was expected that those with CKD would have a greater burden of frailty, cognitive impairment, and co-occurrence of the two conditions; given their higher prevalence of comorbidities, particularly in vascular disease. Further studies should aim to replicate these findings among those with and without CKD in other, diverse population studies with validated measures of frailty and cognitive function to better compare the magnitude of burden.This diverse, nationally-representative study further corroborates the potential vascular underpinnings of the frailty-cognition link demonstrated in prior studies [27][28][29][30]35]. Our findings support those prior studies in that the strongest associations between frailty and cognitive function were found for executive function and processing speed (Cohen's d = -0.44, 95%CI: -0.60, -0.28) compared to other memory-related domains.…”
Section: Discussionsupporting
confidence: 90%
“…Prediction models with traditional risk factors poorly predict mortality for patients with CKD. Models that only use factors such as demographics, lifestyle, and kidney function to predict mortality in patients with CKD have C-statistics ranging from 0.71 to 0.81 [28][29][30]. Therefore, efforts to assess the predictive ability of novel risk factors are needed to improve the accuracy of prediction survival models in CKD [9].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported the performance of 4 prediction tools, namely deep learning, plain Bayesian, RF, and LR, for predicting all-cause mortality in patients with CKD. The study showed that Bayesian networks and LR showed superior prediction abilities [ 21 ]. However, another study reported that plain Bayesian, RF, and LR performed adequately well and showed high sensitivity for screening end-stage renal disease in patients with CKD, which is inconsistent with previous reports [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although controversies still exist [ 30 , 35 , 36 , 37 , 38 ], diagnosis and treatment of VD deficiency [with either nutritional (native) or active forms of VD] have not yet been excluded from nephrology practice and guidelines [ 22 , 31 , 39 , 40 ], and despite the poor quality of available evidence, much data may still support VD use in populations with VD deficiency or certain special characteristics, such as CKD patients [ 36 , 39 , 40 ]. Furthermore, when an optimized prediction tool was recently developed using machine-learning techniques, both parathyroid hormone (PTH) and calcidiol were found to be among the seven variables identified as having the best predictive value for 2-year all-cause mortality in patients with CKD G4-G5 [ 41 ].…”
Section: Introductionmentioning
confidence: 99%